SUPERVISI KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU DI MTS NEGERI 01 OKU SELATAN - Bastoni; Suci Hartati (UNISAN JURNAL, 2024)
This research aims to examine the supervision practices of madrasa heads in improving teacher performance and learning at MTs Negeri 01 Oku Selatan. The research method used is qualitative with a case study approach. Data was collected through interviews, observation and documentation studies. The results of the research show that the supervision practices of the madrasa head at MTs Negeri 01 Oku Selatan have had a positive impact on teacher performance and learning. Direct observation, use of information technology, and collaboration between teachers are important parts of supervision practice. Supervision also has a positive impact on teacher motivation and job satisfaction, as well as creating a conducive learning environment. In conclusion, the supervision practices of madrasah principals have an important role in improving teacher performance and learning. Continuous efforts are needed to improve supervision practices to provide a more positive impact on education in the madrasah.